Application of technological tools and techniques in the translation of images and documents” - Argueta Campos, César Alexander
During the preparation of this project, different translation methods were addressed, as well as online translation tools and free-use software. Throughout the process, the methods were used to translate official documents such as birth certificates and academic transcripts. Likewise, during the practice, knowledge of image editing was used where, for example, for a cover of a National Geographic magazine, the image was cleaned with the words of the source language to pass it to the language that was wanted to be translated as the Target Language, using editing programs like Adobe Photoshop or online editing sites. However, the use of technologies is only a basis for the translator to develop in. During the development of the project, certain translation techniques were adopted where the final process, which is the translation, is obtained. In this sense, each translator reflects in his work the method implemented in his project and his way of working is reflected in the translation. Using different methods such as modulation or transposition, among others.